2018
DOI: 10.3390/cells8010007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Autophagy of Innate Immune Cells on Inflammatory Bowel Disease

Abstract: Autophagy, an intracellular degradation mechanism, has many immunological functions and is a constitutive process necessary for maintaining cellular homeostasis and organ structure. One of the functions of autophagy is to control the innate immune response. Many studies conducted in recent years have revealed the contribution of autophagy to the innate immune response, and relationships between this process and various diseases have been reported. Inflammatory bowel disease is an intractable disorder with unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 156 publications
2
25
0
2
Order By: Relevance
“…Mucin is known as the major component in the intestinal mucus layer, and the intestinal mucosal barrier plays a critical role in maintaining intestinal homeostasis and preventing external damage. Autophagy promotes expression of MUC2 [19,50,51], and OXY induces MUC2 expression in intestinal goblet cells [17]. In this study, we found that OXY activates autophagy and that OXY-induced MUC2 expression is decreased by an ER inhibitor.…”
Section: Discussionsupporting
confidence: 50%
“…Mucin is known as the major component in the intestinal mucus layer, and the intestinal mucosal barrier plays a critical role in maintaining intestinal homeostasis and preventing external damage. Autophagy promotes expression of MUC2 [19,50,51], and OXY induces MUC2 expression in intestinal goblet cells [17]. In this study, we found that OXY activates autophagy and that OXY-induced MUC2 expression is decreased by an ER inhibitor.…”
Section: Discussionsupporting
confidence: 50%
“…In HepG2 cells, it was demonstrated that celastrol promotes Nur77 ubiquitination and induces its translocation to mitochondria, resulting in induction of autophagy and suppression of inflammation [21]. Meanwhile, autophagy represents an effective way to control inflammatory responses and oxidative stress [42,[61][62][63][64][65][66]. In our study, we found that GPA treatment promotes Nur77 translocation from the nucleus to mitochondria, then enhancing Nur77 interaction with TRAF6 and p62 to induce autophagy, resulting in suppression inflammatory and oxidative stress.…”
Section: Discussionsupporting
confidence: 48%
“…Although most members of this microbial community perform beneficial functions, certain pathogenic bacteria can evade this defense barrier and enter intestinal epithelial cells (IECs) (4). IEC-intrinsic innate immune responses limit bacterial invasion and maintain beneficial host-bacterium relationships (5,6), but the cellular processes that control intestinal epithelial interactions with invasive pathogens remain largely unknown. Autophagy is an evolutionarily conserved process in which cytoplasmic pathogens and unwanted components are targeted to the lysosome for degradation (7)(8)(9).…”
mentioning
confidence: 99%